2004
DOI: 10.1002/ejic.200400223
|View full text |Cite
|
Sign up to set email alerts
|

D5h Cu5H5X: Pentagonal Hydrocopper Cu5H5 Containing Pentacoordinate Planar Nonmetal Centers (X = B, C, N, O)

Abstract: Keywords: Ab initio calculations / Density functional calculations / Hydrocopper / Pentacoordinate planar carbon / Electronic structures Pentacoordinate planar nonmetals (PPNs) centered in perfect pentagonal hydrocopper complexes Cu 5 H 5 X (X = B, C, N, O), as determined by density functional theory methods, are presented in this communication. The results obtained in this work complete the hypercoordinate planar carbon series [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(33 citation statements)
references
References 14 publications
1
32
0
Order By: Relevance
“…), schleyer@chem.uga.edu (P.v.R.S. [20][21][22][23][24][25][26][27] Notably, anions with planar hypercoordinate borons, B 8 -and B 9 -, were characterized by photoelectron spectroscopy in the gas phase by Boldyrev, Wang, and co-workers. 28 Their computational study indicated that these species are doubly aromatic, 29 due to the presence of six π and six radial electrons.…”
Section: Introductionmentioning
confidence: 99%
“…), schleyer@chem.uga.edu (P.v.R.S. [20][21][22][23][24][25][26][27] Notably, anions with planar hypercoordinate borons, B 8 -and B 9 -, were characterized by photoelectron spectroscopy in the gas phase by Boldyrev, Wang, and co-workers. 28 Their computational study indicated that these species are doubly aromatic, 29 due to the presence of six π and six radial electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Its electronic configuration is spin singlet. A five‐membered tungsten ring is supported by a planar pentacoordinate carbon atom, which has only been known for coordination to coinage metals or nonmetals thus far 36–39. In this calculated 0 K geometry, the center carbon is slightly off from the plane of the tungsten ring.…”
Section: Resultsmentioning
confidence: 93%
“…The planar hypercoordinate carbon species, including penta-, hexa-and heptacoordinate carbon, have been recently studied by several research groups [209][210][211][212].…”
Section: Ii) Cn 3 Mg 3 + Decompositionmentioning
confidence: 99%